Impact of planned water resource development on current and future water demand of the Koshi river basin, Nepal - Chinnasamy, Pennan; Bharati, Luna; Bhattarai, Utsav; Khadka, Ambika; Dahal, Vaskar; Wahid, S. (Informa UK Limited, 2015)
Water resources of the Koshi Basin (87,311km2) are largely untapped, and while proposals for their development exist, their impacts on current and future water demands are not quantified. The current study is the first to evaluate the impacts of 11 proposed development projects on hydropower generation and water storage. Results revealed that 29733GWh hydropower can be generated and 8382Million m3 (MCM) of water can be stored annually. This can satisfy unmet demands in current (660MCM) basin situation and future scenarios - i.e. population, agricultural and industrial growth – that are projected to have 920, 970 and 1003MCM unmet-demands, respectively by 2050.